An efficient protocol for somatic embryogenesis of garlic (Allium sativum L.) using root tip as explant (Journal of the Bangladesh Agricultural University, 2014)
Genetic improvement of garlic through conventional breeding is very difficult due to sterile nature of its flower. Hence, an alternative system is desirable to induce genetic variation. Tissue culture could be a good opportunities and somatic embryogenesis is one of the potential techniques of tissue culture for in vitro regeneration of garlic plant. The successes and production of somatic embryo depends on several factors such as optimization of media components, genotypes and explant type. Therefore, in the present investigation, garlic root tips were used as explant for callus and somatic embryo induction under different plant growth regulator combination. It was found that MS+1.0 mg l-1 2,4-D was the most favorable (86.10% regeneration with 2.19 cm callus diameter) for callus induction. This concentration also induced and produced good quality somatic embryo. In addition, MS+2.0 mg l-1 Kinetin gave better regeneration of somatic embryo and yielded the highest number (4.670) and longest length (7.0 cm) of shoots per callus. The procedure used a single hormonal signal for callus and somatic embryo induction as well as hormone free medium for further development of plantlet. Besides, maximum duration for callus induction and somatic embryo production was 17 and 10.67 days respectively. Thus, it appears that the protocol is cheap and time bound and particularly useful for conducting experiment for genetic improvement of garlic. Furthermore, as the protocol is cost effective, it can be further tested for commercial feasibility. DOI: http://dx.doi.org/10.3329/jbau.v12i1.20747 J. Bangladesh Agril. Univ. 12(1): 1-6, June 2014